Systematic and Molecular Basis of the Antibacterial Action of Quinoxaline 1,4-Di-N-Oxides against Escherichia coli - Cheng, Guyue; Li, Bei; Wang, Chenxi; Zhang, Hongfei; Liang, Guixia; Weng, Zhifei; Hao, Haihong; Wang, Xu; Liu, Zhenli; Dai, Menghong; Wang, Yulian; Yuan, Zonghui (PLOS ONE, 2015)
Quinoxaline 1,4-di-N-oxides (QdNOs) are widely known as potent antibacterial agents, but their antibacterial mechanisms are incompletely understood. In this study, the transcriptomic and proteomic profiles of Escherichia coli exposed to QdNOs were integratively investigated, and the results demonstrated that QdNOs mainly induced an SOS response and oxidative stress. Moreover, genes and proteins involved in the bacterial metabolism, cellular structure maintenance, resistance and virulence were also found to be changed, conferring bacterial survival strategies. Biochemical assays showed that reactive oxygen species were induced in the QdNO-treated bacteria and that free radical scavengers attenuated the antibacterial action of QdNOs and DNA damage, suggesting an oxidative-DNA-damage action of QdNOs. The QdNO radical intermediates, likely carbon-centered and aryl-type radicals, as identified by electron paramagnetic resonance, were the major radicals induced by QdNOs, and xanthine oxidase was one of the QdNO-activating enzymes. This study provides new insights into the action of QdNOs in a systematic manner and increases the current knowledge of bacterial physiology under antibiotic stresses, which may be of great value in the development of new antibiotic-potentiating strategies.